Analysis of Consumer Perceptions of Marketing Mix Strategies in the Home Industry of "Ayang" Skin Crackers in Mataram City - Oktiani, Asri; Maryanti, Sri (Business Management, 2025)
This research aims to analyze consumer perceptions regarding the implementation of the marketing mix which includes product, price, place and promotion at the Home Industry of Ayang Skin Crackers in Mataram City. The research method used was quantitative descriptive with data collection techniques through observation, interviews, documentation and distributing questionnaires to 70 respondents. Data analysis was carried out using a Likert scale to measure the level of consumer perception. The research results show that consumer perceptions of all aspects of the marketing mix are in the good category, with the product aspect getting the highest assessment, especially in terms of indicators of taste and product variety. Promotion strategies through social media and word of mouth have proven effective in expanding market reach. These findings emphasize the importance of implementing marketing strategies that are adaptive to consumer needs in order to increase customer satisfaction and loyalty. It is hoped that this research can be a reference for small businesses in developing marketing strategies based on consumer perceptions.